2014
DOI: 10.1152/jn.00058.2013
|View full text |Cite
|
Sign up to set email alerts
|

The parietal reach region is limb specific and not involved in eye-hand coordination

Abstract: Primates frequently reach toward visual targets. Neurons in early visual areas respond to stimuli in the contralateral visual hemifield and without regard to which limb will be used to reach toward that target. In contrast, neurons in motor areas typically respond when reaches are performed using the contralateral limb and with minimal regard to the visuospatial location of the target. The parietal reach region (PRR) is located early in the visuomotor processing hierarchy. PRR neurons are significantly modulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
52
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(56 citation statements)
references
References 76 publications
4
52
0
Order By: Relevance
“…A recent inactivation study in PRR found lesion effects specific to contralateral limb movements but independent of the spatial location of the reach goal (Yttri et al 2014). Based on this result, the authors suggested limb-specific movement planning in area PRR and therefore characterized the PRR as a motor area situated early in the visuomotor pathway.…”
mentioning
confidence: 94%
“…A recent inactivation study in PRR found lesion effects specific to contralateral limb movements but independent of the spatial location of the reach goal (Yttri et al 2014). Based on this result, the authors suggested limb-specific movement planning in area PRR and therefore characterized the PRR as a motor area situated early in the visuomotor pathway.…”
mentioning
confidence: 94%
“…In daily manual tasks including simple reaches and grasps, people look at task-relevant objects before acting on them (Johansson et al, 2001;Hayhoe et al, 2003;Ko et al, 2010). The preceding foveation of task-relevant objects provides high-acuity visual information about the position and shape of target objects, enhancing the precision of the following hand movement (Enright, 1995;Johansson et al, 2001;Kato and Fukuda, 2002;Crawford et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The preceding foveation of task-relevant objects provides high-acuity visual information about the position and shape of target objects, enhancing the precision of the following hand movement (Enright, 1995;Johansson et al, 2001;Kato and Fukuda, 2002;Crawford et al, 2004). Consequently, reach errors increase in a gazedependent manner when reach and gaze are spatially decoupled (e.g., reaching for coffee while reading a newspaper; Henriques and Crawford, 2000).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neurons in these areas, as well as in the dorsal portion of area 5 (A5) (Cui and Andersen 2011;Bremner and Andersen 2014), show differential responses to the sum of spatial and effector information. Effector-and spatial-specific deficits are seen after reversible lesions of these areas (Liu et al 2010;Battaglia-Mayer et al 2013;Hwang et al 2012;Yttri et al 2013Yttri et al , 2014. Neurons in the frontal eye fields (FEF) show all 3 properties (responses to pure spatial and to pure effector information; differential responses to combined spatial and effector information; effector-and spatial-specific deficits from lesions) and are known to play a causal role in directing saccades but not reaches (Bruce and Goldberg 1985;Schall 1991;Hanes et al 1998;Snyder 2006, 2009;Wardak et al 2006;Crapse and Sommer 2009;Ray et al 2009).…”
Section: Introductionmentioning
confidence: 99%